Towards safer sport: modern perspectives on cardiovascular screening for the prevention of sudden cardiac death in athletes - Sudomir, Maria; Michałowski, Maciej; Wilkowska, Krystyna; Kaczorowski, Wojciech; Knysak, Karol; Maj, Alicja; Szczerba, Mateusz; Hejnosz, Aleksandra; Jastrzębski, Michał; Piątek, Maja (Quality in Sport, 2025)
Background: Sudden cardiac death (SCD), defined as an unexpected fatal event within 1 hour of symptom onset (witnessed) or 24 hours (unwitnessed), is a leading cause of sport-related mortality, even in apparently healthy athletes. True incidence remains unclear due to variable definitions, reporting heterogeneity, and diagnostic limitations. Understanding mechanisms and risk factors is essential for effective screening and prevention. Aim: This review examines cardiac anomaly screening in athletes, focusing on optimal modalities, target groups, and economic considerations. It also synthesizes evidence on epidemiology, structural and physiological risk factors, prevention strategies, and knowledge gaps. Methods: A narrative review of PubMed and Google Scholar included original research, reviews, meta-analyses, and guidelines. Studies were analyzed for epidemiology, risk factors, pathomechanisms, and prevention strategies to provide an integrated overview. Results: SCD etiology and risk profiles are heterogeneous, limiting universal screening. ECG use remains debated due to cost and false results. Questionnaires and physical exams are widely recommended, but advanced diagnostics face financial and logistical constraints. Reporting inconsistencies, variable athlete definitions, and resource disparities complicate implementation. Conclusions: SCD in athletes arises from diverse cardiovascular disorders, making universal screening difficult. Evidence supports context-dependent, targeted strategies that balance feasibility, equity, and risk reduction.